Design Education in the Post‐Digital Age By John Maeda. (December 2014) - Nussbaum, Bruce
<x xml:space="preserve">Abstract</x> Recently, the Museum of Art and Design (MAD) in New York City put on an exhibition called Materializing the Postdigital. It showcased the original and beautiful clothes and sculptures that can now be designed and created using 3D printing and other digital making technologies. The most powerful message of the exhibition was the title itself because it highlighted, for the first time, the fact that we have finally incorporated a new generation of making technologies and can finally get back to the heart and soul of design—the making itself. Which is why John Maeda's "Design Education in the Post‐Digital Age" is so important. For 20 years, a generation really, designers, entrepreneurs, business managers and professors have been busy struggling with the new technologies of making. It has been a tense and difficult time, particularly in education, where change comes slowly. Maeda aptly highlights these struggles in academia and how the rise of new digital design technologies has led to conflict between older and younger designers and between older professors and younger students. He also states boldly what so many have said quietly, which is that the obsession with digital technology has often led to a segregation of creativity from technology. Or, for those who reject digital technology entirely, it has led to a stifling of creativity. Maeda's message is singularly clear. Let's get on with integrating technology into our process so we can return to our true goals as artists and innovators creating the new and building a better future for people. The growing integration of design with high‐tech startups shows us what can be accomplished.